The Routledge handbook of second language acquisition and input processing - Wong, Wynne; Barcroft, Joe (New York, NY : Routledge, 2024)
"This state-of-the-science handbook offers a comprehensive discussion of input processing in second language acquisition. The volume assesses past and current research on input processing and engages the reader in critical reflection about the current state of the field and what lies ahead for future research, theory-building, and implications for language instruction"--
Keywords: Second language acquisition; LANGUAGE ARTS & DISCIPLINES / Linguistics